Legal Status of Customary Communities, Customary Law Communities and Indigenous Communities as Custom Law Subjects - SIHOTANG, AMRI PANAHATAN; RATO, DOMINIKUS; Izziyana, Wafda Vivid (Journal of Ecohumanism, 2024)
The goal of this study is to examine the legal-statutes of the unity of the adat-law community (customary community) and adat-community as the subject of adat-lawThis is a socio legal research and employed a reflective approach, this study is result and discussion: the result of the reflection base on research conducted in various regions or areas as adatlaw legal-fields and is supported by the writings of researchers, observers, adatlaw and indigenous people activists. The basic concept of this paper is to say that the legal-statutes of the unity of adat-law communities, adat law communities, and adat-communities as the subject of adat law as stated in Article 18 B Paragraph (2) of the 1945 Constitution of the Republic of Indonesia are identical. However, the legal-statutes of the unity adat law communities, adatlaw community, and adat-community needs to be discussed. This discussion was initiated so that the unity of adat-law communities, adat-law communities, adat-communities were not identical. Therefore, it is important to discuss this paper with the aim of clarifying the legal-statutes of the unity of adat-law communities, adat-law communities, and adat-communities as the subject of adat-law.